2022
DOI: 10.3390/s22186745
|View full text |Cite
|
Sign up to set email alerts
|

Smart-Home Concept for Remote Monitoring of Instrumental Activities of Daily Living (IADL) in Older Adults with Cognitive Impairment: A Proof of Concept and Feasibility Study

Abstract: Assessment of instrumental activities of daily living (IADL) is essential for the diagnosis and staging of dementia. However, current IADL assessments are subjective and cannot be administered remotely. We proposed a smart-home design, called IADLSys, for remote monitoring of IADL. IADLSys consists of three major components: (1) wireless physical tags (pTAG) attached to objects of interest, (2) a pendant–sensor to monitor physical activities and detect interaction with pTAGs, and (3) an interactive tablet as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A reduced number of motor tasks may improve the feasibility of using the platform in a non-clinical setting and for remote patient monitoring. Digital health technologies are poised to become an integral part of modern health care, expedited by the surge in remote care necessitated by the COVID-19 pandemic [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The proposed solution paves the way to integrating digital health technology (i.e., wearables) to enhance the utility of objective measures of ataxia.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced number of motor tasks may improve the feasibility of using the platform in a non-clinical setting and for remote patient monitoring. Digital health technologies are poised to become an integral part of modern health care, expedited by the surge in remote care necessitated by the COVID-19 pandemic [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The proposed solution paves the way to integrating digital health technology (i.e., wearables) to enhance the utility of objective measures of ataxia.…”
Section: Discussionmentioning
confidence: 99%
“…Smart home technology, as proposed in a recent literature review, monitors both cognitive functions and ADLs in a simulated home environment [ 9 ], while the installed sensors can detect potential risks and enhance remote clinical assessment [ 10 ]. Therefore, adapting assistive technologies like smart homes to support independent living for people with dementia or early stages such as mild cognitive impairment (MCI), offering applications for memory aid, executive functions, social interactions, and more, constitutes a challenging recent approach [ 11 ]. Several research studies have so far been used to capture daily vital signs and automatically detect ADLs, enhance autonomy, recognize emergencies, and track the disease progression of individuals with cognitive impairment [ 12 , 13 , 14 ] through smart home systems.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover mental activities may protect against mild cognitive impairment. In fact engaging in mentally and physically stimulating activities, even late in life, may protect against new-onset mild cognitive impairment, according to different studies [1][2][3][4][5][6][7][8][9]. Particularly, an interesting study [1] found that cognitively normal people aged 70 years or older who engaged in computer use, craft activities, social activities, and playing games had a decreased risk of developing MCI.…”
Section: The (Mild Cognitive Impairment) MCI Chronic Care Scenariomentioning
confidence: 99%